Towards Future Indications of Therapeutic Utilization of Stem Cells: a Case Report of Application after Hypoxic Encephalopathy - Atabak NAJAFI; Mojtaba MOJTAHEDZADEH; Niayesh MOHEBBI; Parastoo MIRZABEIGI; Legese CHELKEBA; Camelia RAMBOD; Farideh RAZI; Arezoo AHMADI (Tehran University of Medical Sciences, 2015)
To date, stem cell therapy is a novel treatment method especially in irreversible end organ damage. We present a case of a 21-yr-old man, who admitted in Sina Hospital, Tehran University of Medical Sciences, Iran with open left femur fracture following car accident. Developing fat emboli syndrome led to cardiac arrest. Despite of efforts to optimize supportive care and neuroprotective strategies, the level and content of conscious did not improve. We performed stem cell therapy and he was discharged home with mild neurologic deficit on hospital day 116. This is the first case of stem cell therapy applied to a postarrest victim with severe evidently irreversible neurological injuries. This therapy could be considered to improve neurological recovery in patients following cardiac arrest.   Keywords: Cardiopulmonary cerebral resuscitation, Cardiac arrest, Hypothermia, Stem cell therapy